RESOCIALIZATION AND ENTREPRENEURIAL INITIATIVE OF WORK ENGAGED CONVICTED PENALTIES IN VOJVODINA - Brljak, Zoran; Penezić, Nenad; Bobić, Aco (Poslovna ekonomija, 2020)
The research in this paper focuses on the level of re-socialization and entrepreneurial initiative of working convicts in penal institutions, because the expressed entrepreneurial initiative during the execution of a sentence can serve as a basis for employment and easier re-socialization after release from prison. Therefore, the aim of the research is to determine the differences in the level of resocialization and entrepreneurial initiative according to the work engagement of convicts. The sample contains 286 randomly surveyed convicts from penal institutions on the territory of AP Vojvodina. Data were collected and analyzed using the frequency to show the socio-demographic characteristics of convicts and the method of cross-tabulation to determine the differences in the level of resocialization and entrepreneurial initiative according to the work capacity of convicts. The results indicate that convicts who are employed more often have a higher level of pronounced resocialization compared to convicts who are not employed. Also, it was determined that working convicts have a higher level of entrepreneurial initiative, ie. Employed convicts show: higher level of readiness for additional engagement in order to improve living and working conditions in the institution, higher level of readiness for additional engagement in order to obtain a better classification group and higher level of readiness for further education and professional training, compared to non-working convicts engaged in the institution. The implications of the research indicate that it is necessary for employees to work more in penitentiary institutions in terms of attending education and training programs for acquiring entrepreneurial knowledge and skills, which will lead to better social and work resocialization after leaving the penitentiary institution.